Malay traditional society and a colonial encounter - Dahlan, H.M. (Universiti Kebangsaan Malaysia, 1976)
The shift of Nusantara centers after the 16th century and consequently the carving of Nusantara into separate political units after the 19th century were directly related to a series of colonial power struggle in this region, as well as to political and technological changes taking place in the home countries of these powers. Their principal goal was to establish a colonial regime that would look after their economic interests in their newly founded colonies. In essence, that was the inspiring motive behind their colonial satellitization.